2011
DOI: 10.1007/s12149-011-0542-7
|View full text |Cite
|
Sign up to set email alerts
|

High resolution SPECT imaging for visualization of intratumoral heterogeneity using a SPECT/CT scanner dedicated for small animal imaging

Abstract: Objectives Tumor interiors are never homogeneous and in vivo visualization of intratumoral heterogeneity would be an innovation that contributes to improved cancer therapy. But, conventional nuclear medicine tests have failed to visualize heterogeneity in vivo because of limited spatial resolution. Recently developed single photon emission computed tomographic (SPECT) scanners dedicated for small animal imaging are of interest due to their excellent spatial resolution of\1 mm, but few studies have focused on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 24 publications
(31 reference statements)
0
18
0
Order By: Relevance
“…On the other hand, PAH was not suitable for SPECT imaging, as it yielded SPECT images with low resolution. Although Mok et al reported that MPH was appropriate for bone scintigraphy using Tc-MDP with about 67 MBq [8], we expected that SPH would be useful with higher radioactivity because the bone scintigraphy was obtained by SPH using 99m Tc-MDP with about 100 MBq [11] and 185…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…On the other hand, PAH was not suitable for SPECT imaging, as it yielded SPECT images with low resolution. Although Mok et al reported that MPH was appropriate for bone scintigraphy using Tc-MDP with about 67 MBq [8], we expected that SPH would be useful with higher radioactivity because the bone scintigraphy was obtained by SPH using 99m Tc-MDP with about 100 MBq [11] and 185…”
Section: Discussionmentioning
confidence: 92%
“…In current SPECT scanners, cadmium zinc telluride (CZT) semiconductor detectors have been applied to improve energy and spatial resolution [4][5][6][7][8], as compared with sodium iodide (NaI) scintillation detectors, which were used in conventional SPECT scanners [9][10][11][12][13][14][15][16][17][18][19]. Planar and SPECT projection data are acquired using various collimators in clinical settings.…”
Section: Introductionmentioning
confidence: 99%
“…Phospholipid concentration was measured using phospholipid assay kit (Wako, Osaka, Japan). 111 In-DTPA encapsulated PEGylated liposomes were generated by following the remote loading method; specifically, the liposomes encapsulating DTPA were labeled with 111 In (Nihon Medi-Physics, Tokyo, Japan) through incubation with 111 In-oxine (34).…”
Section: Cd31 Signals Merged With Hoechst 33342 Positivity (Pixels) Fmentioning
confidence: 99%
“…The longer blood circulation time provides enhanced entrapment of LCLs in tumors with improved pharmacokinetics [46][47][48]. A number of liposome probes have been radiolabeled with 99m Tc, 111 In, and 67 ga. pegylated liposomes encapsulated with 111 In-diethylenetriaminepentaacetic acid (DTpA) have been used to target solid tumors [49,50]. Radiolabeling was performed by a transchelation reaction between a lipophilic oxine and hydrophilic DTpA ligands.…”
Section: Radiolabeled Liposomes For Spect Imagingmentioning
confidence: 99%